Evaluation of Cognitive Functioning and Laterality in Women with Polycystic Ovary Syndrome - Nevin Sağsöz; Orhan Murat Koçak; Rukiye Ada Bender (Cam & Sakura Medical Journal, 2025)
Objective: To investigate potential differences in laterality and cognitive performance between women with polycystic ovary syndrome (PCOS) and healthy individuals. Material and Methods: Thirty women with PCOS and thirty-four healthy controls were recruited. Beck depression inventory, state and trait anxiety inventory (STAI), hand preference questionnaire, line splitting task (LBT), finger tapping, Rey auditory verbal learning test (RAVLT), and Stroop Test were administered to the patient and control groups. In addition, blood levels of androgens were measured. Results: Although the depression score in the PCOS group was higher than the control group (p=0.048), there was no significant difference in the STAI scores (p>0.05). Stroop scores were found to be significantly lower in the PCOS group (p=0.007, p=0.043, p=0.017). The evaluation of Stroop interference scores and RAVLT scores revealed significant differences in RAVLT 1, RAVLT 2, and RAVLT 8 recognition sub-scores between groups (p=0.003, p=0.002, p=0.038, p=0.010 respectively). The absolute rate of right-handedness was statistically lower in the PCOS group (p=0.04). Only LBT values of absolute right-handed subjects (Hand Preference Questionnaire Score: 13) were involved to compare spatial distribution of attention between the groups. It seems that the bisection judgement bias of the PCOS group shifted slightly to the right (p=0.025). A significant interaction was found between LBT scores and dehydroepiandrosterone levels (p<0.05). Conclusion: Several cognitive domains and laterality seem to be affected in PCOS.